Quality management and integrated total quality in spanish mining: results of an empirical research (2012)
This paper presents the results of an empirical study conducted in Spain among mining companies that hold ISO 9001 certification. The two aims of the study were: first, to think about the situation of quality management in Spanish mining, and secondly to discover if the certification of this systems set a solid base that lead the company in a journey towards total quality management integrated with other management systems as important in this kind of industry as the environmental management or the occupational health and safety management.